THE SOLID MEDICAL WASTE MANAGEMENT ANALYSIS IN PUSKESMAS KOTA JAMBI - Jalius; Suandi; emildan pasai emil (Universitas Jambi, 2021)
Puskesmas is one of the health service facilities which each service produces medical and non-medical waste, both liquid and solid. The improvement of Puskesmas services will indirectly affect the rate of waste generation and composition. The waste produced by this Puskesmas is not properly managed which can cause disease and environmental pollution. The aim of this research is the management of medical waste management at the Jambi City Puskesmas with PERMEN LHK NO 56 IN 2015 concerning the procedures and requirements for the management of hazardous waste materials from health care facilities and creating a solid medical waste management model at the Jambi City Health Center in accordance with the PERMEN LHK NO 56/2015. This research was conducted in all Puskesmas Jambi City, as many as 20 Puskesmas. The type of research used is descriptive research using a qualitative approach. The results showed that the solid medical waste management process at the Jambi City Health Center, starting from the stages of sorting, storing and transporting, was not fully in accordance with the Regulation of the Minister of Environment and Forestry Number: P.56 / MenLHK-Setjen / 2015. Based on the results of the analysis of things that are not in accordance with the regulations, a management model will be made in accordance with Permenlhk P.56 / MenLHK-Setjen / 2015 which is safe, healthy and sustainable. Keywords: Puskesmas, Solid Medical Waste, Waste Management System